2007
DOI: 10.1002/uog.3924
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of fetal cardiac magnetic resonance imaging: preliminary experience

Abstract: Figure 2 Axial true-FISP section demonstrating fetal cardiac ventricular morphology: the most anterior ventricle is the embryological right one, with a trabeculated septal wall (arrow), and the most posterior is the embryological left one, with a smooth septal wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 13 publications
0
41
1
1
Order By: Relevance
“…286,287 Some investigators, by combining these sequences and balanced steady-state free-precession sequences, have achieved better images. 288,289 The development of these more sophisticated sequences, with improved temporal resolution, has enhanced the ability of MRI to evaluate fetal cardiac structure despite fetal motion and rapid fetal heart rates. 290,292 However, although these advanced sequences can generate highly useful information without true gating, this singleshot imaging approach has limited spatial resolution.…”
Section: Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…286,287 Some investigators, by combining these sequences and balanced steady-state free-precession sequences, have achieved better images. 288,289 The development of these more sophisticated sequences, with improved temporal resolution, has enhanced the ability of MRI to evaluate fetal cardiac structure despite fetal motion and rapid fetal heart rates. 290,292 However, although these advanced sequences can generate highly useful information without true gating, this singleshot imaging approach has limited spatial resolution.…”
Section: Acquisitionmentioning
confidence: 99%
“…In summary, with increasingly sophisticated MRI technology, faster imaging sequences, improvements in resolution, and innovative gating algorithms, fetal cardiac MRI has the potential to complement ultrasound imaging in the evaluation of fetal visceroatrial situs, 288,290,294 cardiac structure, 286,[288][289][290][291][292] and cardiac function. 287,292 Although the clinical utility of the technology has not been well established and although it currently is used mostly as a research tool, fetal cardiac MRI is reasonable to perform in the evaluation of certain forms of fetal cardiovascular disease, including heterotaxy and systemic venous anomalies, and in the assessment of associated extracardiac malformations.…”
Section: Acquisitionmentioning
confidence: 99%
“…Due to its noninvasive nature, this present study is far more practicable, particularly in relation to human subjects. Compared with images of prior studies (17)(18)(19), the visualization in this study of the aforementioned anatomical structures demonstrated considerable improvements in the adequacy of the visualization. Prior studies described difficulties with the imaging of main cardiac outflow vessels, such as the aorta with its valve (19).…”
Section: Discussionmentioning
confidence: 86%
“…In-utero MR imaging of the fetal heart 2.2.1 Feasibility and patients' selection MRI of the fetal heart is feasible (Saleem, 2008); however, it has not been thoroughly investigated with only few reports in literature most of them in the form of case reports or preliminary experiences (Gorincour et al, 2007;Kivelitz et al, 2004;Manganaro et al, 2008). We will depend in discussion of MRI of fetal heart in this chapter on findings from our study of 298 pregnancies at high risk for CHD that were enrolled sequentially from September 2003 to August 2010 in our institutional review board-approved study.…”
Section: 2mentioning
confidence: 99%
“…Role of CMR includes anatomic and functional assessment of the cardiovascular system (Finn et al, 2006). Fetal MRI proved valuable in defining the details of fetal anatomy especially the central nervous system (Frates et al, 2004;Levine, 2006;Saleem et al, 2009) and potentially the heart (Gorincour et al, 2007;Saleem, 2008). However, CMR has not been thoroughly investigated in-utero.…”
Section: Introductionmentioning
confidence: 99%